Virtual 3D World Construction by Inter-connecting Photograph-based 3D Models - Aoki, Takashi; Tanikawa, Tomohiro; Hirose, Michitaka (2008 IEEE Virtual Reality Conference, 2008)
We present a novel approach for constructing a virtual 3D world from a sparse set of 2D photograph images. In our approach, we do not construct a large 3D world directly from the images, instead we construct several 3D models from the images and inter-connect them. Each 3D model is photograph-based 3D model that constitutes a few faces and a high-resolution photographic texture image. By arranging some photograph-based 3D models in a 3D scene, we construct a virtual 3D world. To inter-connect these 3D models and represent a unified 3D world, we render the 3D models by blending them together according to view-point position and rotation. Using our novel approach, it is possible to semi-automatically construct a virtual 3D world from fewer photograph images.